Paper No P11: Nanoparticles‐ and Ionic Liquid‐Modified Liquid Crystal Systems for Spatial Light Modulators. Issue 1 (September 2015) - Czajkowski, M.; Cybinska, J.; Klajn, J.; Feder‐Kubis, J.; Gordel, M.; Komorowska, K.
Abstract We present some approaches for modulation of light by hybrid liquid crystal materials. Mixtures of liquid crystals with chiral ionic liquids are used for modulating the incident light amplitude by alternative electric field. Hybrid cells of liquid crystals with inner surfaces, being modified by metallic and semiconductor nanoparticles, are used for phase or amplitude modulation of light. Those groups of the materials used for modification of liquid crystal cells are promising for construction of efficient light switches and modulators.